Predictors of Death Penalty Views in China: An Empirical Comparison Between College Students and Citizens - Jiang, Shanhe (International journal of offender therapy and comparative criminology, 2018)
China's current Criminal Law has 46 death-eligible offenses, and China executes more people than any other country in the world. However, there is a lack of study of attitudes toward capital punishment for specific offenses, and no death penalty view comparison between college students and regular citizens in China was found. This study was taken to address these limitations. Using a sample of 401 respondents from Zhejiang, China, in 2016, the present study found that more than 72% of respondents favored the death penalty without any specification of crime types. Level of death penalty support differed by various specific crimes. As expected, relative to college students, general population citizens were more likely to support capital punishment. Both groups had the highest death penalty support for murder. The study also revealed similar and different reasons behind death penalty attitudes between college students and regular citizens.